Discovery of Novel IDH1 Inhibitor Through Comparative Structure-Based Virtual Screening - Wang, Yuwei; Tang, Shuai; Lai, Huanling; Jin, Ruyi; Long, Xu; Li, Na; Tang, Yuping; Guo, Hui; Yao, Xiaojun; Leung, Elaine Lai-Han (Frontiers in Pharmacology, 2020)
IDH1 mutations occur in about 20–30% of gliomas and are a promising target for the treatment of cancer. In the present study, the performance of aIDH1R132H was verified via glide-docking-based virtual screening. On the basis of the two crystal structures (5TQH and 6B0Z) with the best discriminating ability to identify IDH1R132H inhibitors from a decoy set, a docking-based virtual screening strategy was employed for identifying new IDH1R132H inhibitors. In the end, 57 structurally diverse compounds were reserved and evaluated through experimental tests, and 10 of them showed substantial activity in targeting IDH1R132H (IC50 < 50 μM). Molecular docking technology showed that L806-0255, V015-1671, and AQ-714/41674992 could bind to the binding pocket composed of hydrophobic residues. These findings indicate that L806-0255, V015-1671, and AQ-714/41674992 have the potential as lead compounds for the treatment of IDH1-mutated gliomas through further optimization.